Cooperation of security services of SFRY with services of other countries after the Brioni plenum until the mid 80s of the 20th century - Lazić Radojica S. (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2018)
This paper researches and analyses cooperation of security services of SFRY with security services of other countries, from the Brioni plenum, i.e., in the second half of 1966, until the mid 80s of the 20th century. Starting from the policy of the then state and political leadership, the paper analyses the results of cooperation realized with security services of western and NATO countries, countries of the Warsaw Pact, Non-aligned countries, as well as other countries and freedom movements. State security services of the Socialist Federative Republic of Yugoslavia played an active role in cooperation of many security services in various parts of the world. The priority in this cooperation were freedom movements which the then Yugoslav authorities supported heartily, 'through strategic orientation of its foreign and internal policy in the struggle for independence and as a decisive factor for peace and security in Europe and the world'. In accordance with the proclaimed principles, cooperation with foreign security services was based primarily on principles of equality, independence, non-involvement in internal problems of other countries and mutual respect and solidarity. It ran on bilateral basis, with the aim to strengthen and promote security interests of Yugoslavia, affirm its international position and pro-active role in international relations, especially within the framework of the Non-Aligned Movement.